DISPERSION AND SORPTION CHARACTERISTICS OF URANIUM IN THE ZEOLITE-QUARTZ MIXTURE AS BACKFILL MATERIAL IN THE RADIOACTIVE WASTE REPOSITORY - Herry Poernomo; Noor Anis Kundari (Universitas Gadjah Mada, 2006)
The experiment of sorption and dispersion characteristics of uranium in the zeolite-quartz mixture as candidate of raw material of backfill material in the radioactive waste repository has been performed. The objective is to know the effect of zeolite and quartz grain size on the zeolite-to-quartz weight ratio that gives porosity (ε), permeability (K), and dispersivity (α) of uranium in the zeolite-quartz mixture as backfill material. The experiment was carried out by fixed bed method in the column filled by the zeolite-quartz mixture with zeolite-to-quartz weight percent ratio of 100/0, 80/20, 60/40, 40/60, 20/80, 0/100 wt. % in the water saturated condition flowed by uranyl nitrate solution of 500 ppm concentration (Co) as uranium simulation which was leached from immobilized radioactive waste in the repository. The concentration of uranium in the effluents represented as Ct were analyzed by spectrophotometer Corning Colorimeter 253 every 15 minutes, then using Co and Ct uranium dispersivity (α) in the backfill material was determined. The experiment data shown that 0.196 mm particle size of zeolite and 0.116 mm particle size of quartz on the zeolite-to-quartz weight ratio of 60/40 wt. % with ε = 0.678, K = 3.345x10-4 cm/second, and α = 0.759 cm can be proposed as candidate of raw material of backfill material in the radioactive waste repository.